2023
DOI: 10.3390/ijerph20032090
|View full text |Cite
|
Sign up to set email alerts
|

Association of Individual and Neighborhood Characteristics to Problematic Internet Use among Youths and Adolescents: Evidence from Vietnam

Abstract: Introduction: This study aimed to determine latent profiles from the Problematic Internet Use Questionnaire Short Form-6 (PIUQ-SF-6) score of Vietnamese youths and adolescents, which supports the diagnosis of problematic internet use among a large sample size. Moreover, it also explored factors that affect each latent profile of the PIUQ-SF-6 score among participants. Methods: A sample of 1477 Vietnamese people, aged 14 to 24, across five provinces participated in the study. Multinomial logistic regression det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Fourth, studies showed that living alone ( Achab et al, 2011 ; Chi et al, 2020 ; Savolainen et al, 2020 ) is a risk factor for IA during the pandemic. For example, a study on 1,477 youth in Vietnam showed that living alone was associated with a higher risk of IA ( Nguyen et al, 2023 ). In addition, compared to those living with family or roommates, Hong Kong university students who lived alone experienced more severe stress, anxiety, and depression during the epidemic ( Shek et al, 2022a ), which might trigger their higher IA.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, studies showed that living alone ( Achab et al, 2011 ; Chi et al, 2020 ; Savolainen et al, 2020 ) is a risk factor for IA during the pandemic. For example, a study on 1,477 youth in Vietnam showed that living alone was associated with a higher risk of IA ( Nguyen et al, 2023 ). In addition, compared to those living with family or roommates, Hong Kong university students who lived alone experienced more severe stress, anxiety, and depression during the epidemic ( Shek et al, 2022a ), which might trigger their higher IA.…”
Section: Introductionmentioning
confidence: 99%